Role of adipokinetic hormone in the Colorado potato beetle, Leptinotarsa decemlineata infected with the entomopathogenic nematode Steinernema carpocapsae. - Hlávková, Daniela (Jihočeská univerzita, 2023)
The study investigates the involvement of adipokinetic hormone (AKH) in the Colorado potato beetle's Leptinotarsa decemlineata (Say, 1824) (Coleoptera: Chrysomelidae) responsive reactions to infection of the entomopathogenic nematode Steinernema carpocapsae (Weiser, 1955) (Rhabditida: Steinernematidae). The findings show that nematode presence doubles the amount of AKH in the central nervous system of L. decemlineata, indicating mobilization of anti-stress reactions in the body. Moreover, the external co-application of Peram-CAH-II with the nematode significantly increased beetle mortality. Therefore, the paper investigates possible mechanisms underlying these phenomena and suggests that the nematodes may benefit from the observed mobilization of metabolites from the fat body into the Peram-CAH-II-induced hemolymph, which provides them with a more nutrient-dense substrate for propagation. These findings could serve in the development suitable insect pest control methods in the future.
Role of adipokinetic hormone in the Colorado potato beetle, Leptinotarsa decemlineata infected with the entomopathogenic nematode Steinernema carpocapsae.
Keywords: AKH; Metabolism; Mortality; Nutrients; Vitellogenin; AKH; Metabolism; Mortality; Nutrients; Vitellogenin